CYTOPATHOGENICITY OF INFLUENZA VIRUS (H4 N3) - AL-HYALI, H. M. I. (The Iraqi Journal of Veterinary Medicine, 2021)
Monolayer tissue cultures of chicken embryo fibroblast ( CEF ) cells infected with avian influenza virus isolate were examined by the hematoxylie and eosin (H&E) staining and indirect immunoperoxidase test for studying the cytopathogenic effect of the virus. Cytopathological changes which occurred in the uncleus of infected cells included nuclear and nucleolar hypertropy, chromatin margination and intranuclear inclusions. The most striking cytoplasmic change were the presence of perinuclear. eosinophilic inclusions at 22-36 hours post inoculation ( p. i.). Vacuolization, and granulation were also observed. Indirect immunoperoxidase ( IP ) test demonstrated the localization of influenza virus antigens in infected cells. A positive peroxidase reaction observed in the nucleus and cytoplasm were similar to those shown hematoxyline and eosin staining.